2021
DOI: 10.1109/access.2021.3134331
|View full text |Cite
|
Sign up to set email alerts
|

The Modeling and Investigation of Slot Skews and Supply Imbalance on the Development of Principal Slotting Harmonics in Squirrel Cage Induction Machines

Abstract: A discrete winding function analysis (DWFA) based approach for the modelling of skewed rotor cage-type induction motor with minimal simulation time is presented in this paper. The rotor slot skew has a significant attenuating impact on principal slotting harmonics (PSH) or rotor slotting harmonics (RSH). These harmonics can play a significant role in sensor-less speed estimation and condition monitoring of induction machines. The advanced fault diagnostic algorithms are becoming increasingly dependent on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(49 reference statements)
1
5
0
Order By: Relevance
“…The proposed skew method Improved air gap permeance modelling exhibits the desired torque ripple reduction (Kawase et al, 2009). As rotor skew increases, the length and the resistance of the rotor bars increase, which reduces the average torque at the rated slip to a minor extent as observed (Darjazini et al, 2021;Asad et al, 2021). In contrast, Kawase et al (2009) observed an optimum of the average torque for a skew of one rotor slot pitch.…”
Section: Implementation In Magnetic Equivalent Circuitsmentioning
confidence: 86%
“…The proposed skew method Improved air gap permeance modelling exhibits the desired torque ripple reduction (Kawase et al, 2009). As rotor skew increases, the length and the resistance of the rotor bars increase, which reduces the average torque at the rated slip to a minor extent as observed (Darjazini et al, 2021;Asad et al, 2021). In contrast, Kawase et al (2009) observed an optimum of the average torque for a skew of one rotor slot pitch.…”
Section: Implementation In Magnetic Equivalent Circuitsmentioning
confidence: 86%
“…Their versatility, manageability, remarkable energy efficiency, better power quality, and other outstanding qualities lead to their extensive use [6]. The addition of reactive power compensators enhances the complexity of wind energy conversion systems, which include double cage induction machines (DCIMs) and single cage induction machines (SCIMs) [7], [8]. When using a SCIM with two squirrel cages instead of one with one cage, the order and complexity increase exponentially.…”
Section: Introductionmentioning
confidence: 99%
“…The main property of MEC model is to consider the magnetic saturation in iron parts. Other analytical techniques such as winding function theory [2], sub‐domain model [3], conformal mapping (CM) method [4], and field reconstruction method [5] cannot consider the magnetic saturation.…”
Section: Introductionmentioning
confidence: 99%